Deoxycholate is an important releaser of peptide YY and enteroglucagon from the human colon. Issue 9 (September 1993) - Adrian, T E; Ballantyne, G H; Longo, W E; Bilchik, A J; Graham, S; Basson, M D; Tierney, R P; Modlin, I M
Abstract : Peptide YY (PYY) and enteroglucagon are hormonal peptides found in endocrine cells of the distal intestinal mucosa. Although it is known that plasma concentrations of both peptides increase in response to feeding, the mechanism by which ingested food causes release of colonic hormones is not understood. The release of PYY and enteroglucagon was measured in response to intraluminal stimuli in 176 patients having investigative colonoscopy. Introduction of air, saline (isotonic and hypertonic), glucose (isotonic and hypertonic), oleic acid (without bile salts), and casein hydrolysate all failed to release PYY but glucose caused a small but significant increase in enteroglucagon concentrations. In contrast with the lack of effect of nutrients, infusion of deoxycholic acid produced a rapid and marked dose responsive increase in plasma PYY concentrations when introduced into the sigmoid colon. PYY release was statistically significant at doses between 3.3 mM to 30 mM; for example 10 mM deoxycholate caused a sixfold increase in plasma PYY concentrations. Infusion of 10 mM deoxycholate into the transverse colon or caecum produced an increase of PYY that was similar to the responses in the sigmoid colon. There was also a significant release of enteroglucagon in response to infusion of this bile salt into the sigmoid colon at doses between 3.3 mM and 30 mM. The enteroglucagon response to 10 mM deoxycholate was similar in all three colonic regions. When oleic acid was added to deoxycholate as an emulsion, the release of PYY and enteroglucagon was similar to that seen with the bile salt alone. These findings suggest that bile salts may play an important part in the control of colonic endocrine function and may explain the increased circulating concentrations of colonic regulatory peptides that are seen in malabsorption states and after small bowel resection in humans.